SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A Functional Response in Resource Selection Links Multiscale Responses of a Large Carnivore to Human Mortality Risk - Kyle D. Dougherty; Justin A. Dellinger; Bogdan Cristescu; Daniel J. Gammons; David K. Garcelon; J. Mark Higley; Quinton E. Martins; Seth P. D. Riley; Jeff A. Sikich; Thomas R. Stephenson; T. Winston Vickers; Greta M. Wengert; et al. (Ecology Letters, 2025)
Theory suggests that animals make hierarchical, multiscale resource selection decisions to address the hierarchy of factors limiting their fitness. Ecologists have developed tools to link population‐level resource selection across scales; yet, theoretical expectations about the relationship between coarse‐ and fine‐scale selection decisions at the individual level remain elusive despite their importance to fitness. With GPS‐telemetry data collected across California, USA, we evaluated resource selection of mountain lions ( Puma concolor ; n = 244) relative to spatial variation in human‐caused mortality risk. With hierarchical resource selection, coarse‐scale selection determines availability at finer scales. This simple relationship allowed us to demonstrate that functional responses in resource selection explicitly link individual‐level resource selection decisions across scales. We show that individuals proactively avoiding risk when selecting home ranges are freed to relax this avoidance when making decisions within home ranges. However, individuals also exhibit reactive avoidance of risk at the finest scales along movement paths.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

A simple Landsat–MODIS fusion approach for monitoring seasonal evapotranspiration at 30 m spatial resolution - Nishan Bhattarai; Lindi J. Quackenbush; Mark Dougherty; Luke J. Marzen (International Journal of Remote Sensing, 2015)

The impact of forest to urban land conversion on streamflow, total nitrogen, total phosphorus, and total organic carbon inputs to the converse reservoir, Southern Alabama, USA - Emile Elias; Mark Dougherty; Puneet Srivastava; David Laband (Urban Ecosystems, 2013)

Short-term soil nutrient impact in a real-time drain field soil moisture–controlled SDI wastewater disposal system - Jiajie He; Mark Dougherty; Francisco J. Arriaga; John P. Fulton; Charles W. Wood; Joey N. Shaw; Clifford R. Lange (Irrigation Science, 2013)

Increased leaf area dominates carbon flux response to elevated CO 2 in stands of Populus deltoides (Bartr.) - Ramesh Murthy; Greg Barron‐Gafford; Phillip M. Dougherty; Victor C. Engel; Katie Grieve; Linda Handley; Christie Klimas; Mark J. Potosnak; Stanley J. Zarnoch; Jianwei Zhang (Global Change Biology, 2005)
We examined the effects of atmospheric vapor pressure deficit (VPD) and soil moisture stress (SMS) on leaf‐ and stand‐level CO 2 exchange in model 3‐year‐old coppiced cottonwood ( Populus deltoides Bartr.) plantations using the large‐scale, controlled environments of the Biosphere 2 Laboratory. A short‐term experiment was imposed on top of continuing, long‐term CO 2 treatments (43 and 120 Pa), at the end of the growing season. For the experiment, the plantations were exposed for 6–14 days to low and high VPD (0.6 and 2.5 kPa) at low and high volumetric soil moisture contents (25–39%). When system gross CO 2 assimilation was corrected for leaf area, system net CO 2 exchange (SNCE), integrated daily SNCE, and system respiration increased in response to elevated CO 2 . The increases were mainly as a result of the larger leaf area developed during growth at high CO 2 , before the short‐term experiment; the observed decline in responses to SMS and high VPD treatments was partly because of leaf area reduction. Elevated CO 2 ameliorated the gas exchange consequences of water stress at the stand level, in all treatments. The initial slope of light response curves of stand photosynthesis (efficiency of light use by the stand) increased in response to elevated CO 2 under all treatments. Leaf‐level net CO 2 assimilation rate and apparent quantum efficiency were consistently higher, and stomatal conductance and transpiration were significantly lower, under high CO 2 in all soil moisture and VPD combinations (except for conductance and transpiration in high soil moisture, low VPD). Comparisons of leaf‐ and stand‐level gross CO 2 exchange indicated that the limitation of assimilation because of canopy light environment (in well‐irrigated stands; ratio of leaf : stand=3.2–3.5) switched to a predominantly individual leaf limitation (because of stomatal closure) in response to water stress (leaf : stand=0.8–1.3). These observations enabled a good prediction of whole stand assimilation from leaf‐level data under water‐stressed conditions; the predictive ability was less under well‐watered conditions. The data also demonstrated the need for a better understanding of the relationship between leaf water potential, leaf abscission, and stand LAI.